Special composite high-temperature wear-resistant gradient coating for titanium alloy knife edge and preparation method thereof

By using laser cladding technology to form a composite high-temperature wear-resistant gradient coating of Ni-Ti transition coating and Co-based alloy coating on the surface of titanium alloy tools, the problem of titanium alloy tools being prone to cracks and coating falling off under high temperature conditions is solved, and significant improvements in high temperature and wear resistance are achieved.

CN119710677APending Publication Date: 2025-03-28XIAN SURFACE MATERIAL PROTECTION CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411916286.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Titanium alloy tools are prone to cutter cracks and friction losses under high temperature and high resistance conditions, resulting in a shortened service life. In the prior art, such as brazing, it is difficult to effectively solve the cracking and shedding of Co-based alloy coatings.

Method used

Laser cladding technology is used to form a composite high-temperature wear-resistant gradient coating on the surface of the titanium alloy cutting edge. By setting a Ni-Ti transition coating between the Co-based alloy coating and the titanium alloy cutting edge, the gradient changes of Ti and Ni elements are controlled to avoid the formation of brittle phases, thereby improving the interface bonding strength and reducing the cracking sensitivity of the Co-based alloy coating.

Benefits of technology

It significantly improves the high temperature and wear resistance of titanium alloy tools, extends the service life, and successfully prevents the fall off and cracking of the Co-based alloy coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710677A_ABST
    Figure CN119710677A_ABST
Patent Text Reader

Abstract

The invention discloses a composite high-temperature wear-resistant gradient coating special for a titanium alloy knife edge. The composite high-temperature wear-resistant gradient coating comprises a Ni-Ti transition coating, a Co-based alloy coating and a Co-based ceramic composite wear-resistant coating which are sequentially arranged on the surface of the titanium alloy knife edge in a laser cladding mode. The preparation method comprises the following steps: 1, polishing and cleaning a titanium alloy knife edge; 2, Co-based ceramic composite wear-resistant coating powder is prepared; 3, drying the raw material powder; and fourthly, the dried powder serves as raw materials, and laser cladding of a Ni-Ti transition coating, a Co-based alloy coating and a Co-based ceramic composite wear-resistant coating is sequentially conducted on the treated titanium alloy knife edge. By controlling the gradient change of the contents of Ti and Ni elements in the Ni-Ti transition coating, Ti and Co elements are prevented from being combined to form a brittle phase, the cracking sensitivity of the Co-based alloy coating is reduced, and falling is prevented; according to the laser cladding method, the heat input amount is controllable, and the bonding strength of the coating and the titanium alloy knife edge base body is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser cladding coatings, and in particular relates to a composite high-temperature wear-resistant gradient coating specially used for titanium alloy blades and a preparation method thereof. Background Art

[0002] High strength, low density and excellent corrosion resistance are the main characteristics of titanium alloys, which make them widely used in aerospace, shipbuilding and automotive fields. In addition, cutting tools made of titanium alloy materials are also emerging in many industries. However, titanium alloys have low hardness and poor friction performance, especially low friction and wear resistance. Adhesion wear is very easy to occur during the friction process. At the same time, in many working conditions, titanium alloy cutting tools need to face harsh working conditions such as high temperature and high resistance during service, which causes cracks at the cutting edge and friction loss, thus affecting their service life. In order to reduce the wear of the cutting tool, increase the service life and processing efficiency of the cutting tool under harsh working conditions such as high temperature and high resistance, coating the cutting edge surface has become an important way to improve the performance of the cutting tool.

[0003] Co-based alloy is a hard alloy that can resist various types of wear and corrosion as well as high-temperature oxidation. Brazing is commonly used to weld Co-based alloy materials at the blade of a steel knife to improve its high-temperature resistance and wear resistance. However, the strength of the brazed joint is low and the heat resistance is poor, which can easily cause the Co-based alloy materials welded at the blade to fall off. Compared with brazing technology, laser cladding has the advantages of high cooling rate, small heat-affected zone, fine grains of the cladding layer, and metallurgical bonding. Therefore, laser cladding technology is used as a coating preparation technology. In addition, the surface of titanium alloy materials clad with Co-based alloys often faces problems such as cracking, falling off, and poor interface bonding strength.

[0004] Therefore, it is urgently necessary to invent a coating system and a preparation method for cladding Co-based alloy on the surface of titanium alloy materials, in order to improve the high temperature resistance and wear resistance of titanium alloy tools, and to meet the application requirements under complex working conditions of high temperature resistance and wear resistance, thereby greatly prolonging their service life. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a composite high-temperature wear-resistant gradient coating for titanium alloy blades in view of the deficiencies of the above-mentioned prior art. The high-temperature wear-resistant gradient coating improves the bonding force between the coating and the substrate by setting a Ni-Ti transition coating with similar composition between the titanium alloy blade and the Co-based alloy coating, and by controlling the gradient change of the Ti and Ni element contents in the Ni-Ti transition coating, avoids the combination of Ti and Co elements to form a CoxTiy brittle phase, reduces the cracking sensitivity of the Co-based alloy coating, effectively improves the interface bonding strength, prevents the Co-based alloy coating from falling off, and solves the problem that it is difficult to melt Co-based alloy on the surface of titanium alloy materials.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a composite high-temperature wear-resistant gradient coating specially used for titanium alloy cutting edges, characterized in that it comprises a Ni-Ti transition coating, a Co-based alloy coating and a Co-based ceramic composite wear-resistant coating which are sequentially laser-clad on the surface of the titanium alloy cutting edge; the composition of the Ni-Ti transition coating shows a trend of a gradual decrease in Ti element content and a gradual increase in Ni element content along the direction from the titanium alloy cutting edge to the Co-based alloy coating.

[0007] The composite high-temperature wear-resistant gradient coating of the present invention comprises a Ni-Ti transition coating, a Co-based alloy coating and a Co-based ceramic composite wear-resistant coating. By adding a Ni-Ti transition coating mainly composed of Ni and Ti elements between a titanium alloy blade and a Co-based alloy coating, the bonding force between the coating and the substrate is improved by utilizing the similarity between the Ni-Ti transition coating and the titanium alloy blade substrate material composition. By controlling the composition of the Ni-Ti transition coating to show a trend of a gradual decrease in Ti element content and a gradual increase in Ni element content along the direction from the titanium alloy blade substrate to the Co-based alloy coating, the formation of Co is effectively avoided by combining Ti and Co elements. x Ti y Brittle phase, thus forming a good transition with the Co-based alloy coating, reducing the cracking sensitivity of the Co-based alloy coating; at the same time, more Ti elements at the interface make the Ni-Ti transition coating and the titanium alloy blade substrate form a good metallurgical bond, effectively improving the interface bonding strength, and further preventing the Co-based alloy coating from falling off. In addition, the present invention gives the titanium alloy blade a higher hardness, wear resistance and high temperature resistance through the Co-based alloy coating, and further improves the hardness and wear resistance of the entire coating through the Co-based ceramic composite wear-resistant coating containing a ceramic phase.

[0008] The above-mentioned composite high-temperature wear-resistant gradient coating specially used for titanium alloy blades is characterized in that the composition of the Ni-Ti transition coating is Ni20Ti coating, Ni50Ti coating, Ni80Ti coating, and Ni-based alloy coating in the direction from the titanium alloy blade to the Co-based alloy coating.

[0009] The above-mentioned composite high-temperature wear-resistant gradient coating for titanium alloy blades is characterized in that the raw material for preparing the Ni20Ti coating is Ni20Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 2:8, the raw material for preparing the Ni50Ti coating is Ni50Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 5:5, the raw material for preparing the Ni80Ti coating is Ni80Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 8:2, and the raw material for preparing the Ni-based alloy coating is Ni-based alloy powder with a particle size of 45μm to 106μm and a hardness lower than 250HV. The raw material powders for preparing each layer in the Ni-Ti transition coating of the above-mentioned particle size have excellent fluidity, are not easy to block powder, and are convenient for laser cladding. By controlling the hardness of the Ni-based alloy powder, the coating cladding internal stress is prevented from being excessive and cracking.

[0010] The above-mentioned composite high-temperature wear-resistant gradient coating for titanium alloy blades is characterized in that the raw material for preparing the Co-based alloy coating is Stellite 6 or Stellite 12 Co-based alloy powder with a particle size of 45 μm to 150 μm. In practice, the raw material for preparing the Co-based alloy coating can also be other Co-based alloy powders with similar composition and hardness to Stellite 6 or Stellite 12.

[0011] The above-mentioned composite high-temperature wear-resistant gradient coating specially used for titanium alloy blades is characterized in that the raw materials for preparing the Co-based ceramic composite wear-resistant coating include Co-based alloy powder and ceramic powder, wherein the Co-based alloy powder is of the same type as the raw material for preparing the Co-based alloy coating, the ceramic powder is selected from nitride TiN, carbide TiC, WC-xCo or boride TiB2, and the particle size of the ceramic powder is 15μm to 45μm; the mass proportion of the ceramic phase in the Co-based ceramic composite wear-resistant coating is 20% to 40%.

[0012] The above-mentioned composite high-temperature wear-resistant gradient coating specially used for titanium alloy blades is characterized in that the thickness of the Ni20Ti coating is 0.2mm~0.4mm, the thickness of the Ni50Ti coating is 0.3mm~0.4mm, the thickness of the Ni80Ti coating is 0.3mm~0.4mm, the thickness of the Ni-based alloy coating is 0.4mm~0.6mm, the thickness of the Co-based alloy coating is 0.4mm~0.7mm, and the thickness of the Co-based ceramic composite wear-resistant coating is 0.8mm~1.2mm.

[0013] At the same time, the present invention also discloses a method for preparing the composite high-temperature wear-resistant gradient coating as mentioned above, characterized in that the method comprises the following steps:

[0014] Step 1: grinding the titanium alloy blade, and then using anhydrous ethanol for ultrasonic cleaning to remove surface impurities and oxides and increase the roughness to obtain a treated titanium alloy blade;

[0015] Step 2: ball-milling the Co-based alloy powder and the ceramic powder in an Ar atmosphere to obtain a Co-based ceramic composite wear-resistant coating powder;

[0016] Step 3, the Co-based ceramic composite wear-resistant coating powder obtained in step 2, as well as Ni20Ti powder, Ni50Ti powder, Ni80Ti powder, Ni-based alloy powder, and Co-based alloy powder are placed in a vacuum dryer for drying and dehumidification to obtain dried powders; the drying and dehumidification temperature is 100° C. and the time is 2 hours;

[0017] Step 4: Under an argon atmosphere, using the dried powders obtained in step 3 as raw materials, laser cladding of Ni-Ti transition coating, Co-based alloy coating and Co-based ceramic composite wear-resistant coating is performed in sequence on the treated titanium alloy blade obtained in step 1 to form a composite high-temperature wear-resistant gradient coating.

[0018] The above method is characterized in that the grinding balls used for ball milling and mixing in step 2 are stainless steel grinding balls, and the ball-to-material ratio is 1 to 2:5, the ball milling time is 2h to 3h, and the ball milling speed is 200r / min to 250r / min; the oxygen content in the argon atmosphere in step 4 is less than 100ppm.

[0019] The above method is characterized in that the laser cladding process parameters of the Ni-Ti transition coating are: laser power 0.8kW~1.0kW, scanning speed 12mm / s~14mm / s, overlap rate 60%, powder carrier gas flow rate 6L / min~8L / min, powder feeding speed 7g / min~8g / min, spot diameter 2mm.

[0020] The above method is characterized in that the laser cladding process parameters of the Co-based alloy coating and the Co-based ceramic composite wear-resistant coating are: laser power 1.2kW~1.4kW, scanning speed 12mm / s~16mm / s, overlap rate 50%, powder carrier gas flow rate 6L / min~8L / min, powder feeding speed 7g / min~10g / min, spot diameter 2mm.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] 1. The present invention provides a Ni-Ti transition coating between the titanium alloy blade and the Co-based alloy coating, and utilizes the similarity between the Ni-Ti transition coating and the titanium alloy blade substrate material composition to improve the bonding force between the coating and the substrate. By controlling the gradient change of the Ti and Ni element contents in the Ni-Ti transition coating, the Ti and Co elements are prevented from combining to form a CoxTiy brittle phase, thereby forming a good transition with the Co-based alloy coating, reducing the cracking sensitivity of the Co-based alloy coating, and forming a good metallurgical bond between the Ni-Ti transition coating and the titanium alloy blade substrate, thereby effectively improving the interface bonding strength and further preventing the Co-based alloy coating from falling off.

[0023] 2. The present invention laser-clads gradient layers of different thicknesses, namely, Ni-Ti transition coating, Co-based alloy coating and Co-based ceramic composite wear-resistant coating, on the surface of the titanium alloy blade. By optimizing and rationally compounding the components of each gradient layer, the composition and structure of the coating are guaranteed to change in a gradient manner, which effectively reduces the residual stress in the composite high-temperature wear-resistant gradient coating, reduces the tendency of the coating to crack, and successfully realizes the preparation of the Co-based alloy coating on the surface of the titanium alloy blade.

[0024] 3. The composite high-temperature wear-resistant gradient coating of the present invention effectively improves the mismatch between the thermal expansion coefficients of the titanium alloy blade substrate and the coating, reduces residual stress, avoids defects such as pores, cracks, and shedding in the coating, and improves the high-temperature resistance, toughness, and wear resistance of the titanium alloy blade, thereby extending its service life.

[0025] 4. The present invention adopts a laser cladding method to prepare a composite high-temperature wear-resistant gradient coating on a titanium alloy blade. Laser is used as a heat source and reasonable process parameters are combined to make the heat input controllable, ensuring that the coating raw material powder and the titanium alloy blade matrix have sufficient time to react after melting, which helps to improve the bonding strength between the coating and the titanium alloy blade matrix, while reducing the deformation of the titanium alloy blade matrix.

[0026] 5. The present invention uses laser cladding to achieve the successful preparation of Co-based alloy coating on titanium alloy material, and the thickness of the entire coating can reach more than 2.4 mm, the hardness can reach 600HV~800HV, and the wear resistance is greatly improved. At the same time, the composite coating is metallurgically bonded to the substrate, and the interface bonding strength is higher. Compared with brazing, thermal spraying and other technologies, the composite coating prepared by laser cladding did not fall off or crack after being used 300 times under high-temperature conditions, effectively extending the service life of the composite coating.

[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the structure of the composite high-temperature wear-resistant gradient coating specially used for titanium alloy blades of the present invention. DETAILED DESCRIPTION

[0029] Example 1

[0030] like Figure 1 As shown, the composite high-temperature wear-resistant gradient coating dedicated to the titanium alloy blade in this embodiment includes a Ni-Ti transition coating, a Co-based alloy coating, and a Co-based ceramic composite wear-resistant coating that are sequentially laser-clad on the surface of the titanium alloy blade; the composition of the Ni-Ti transition coating is a Ni20Ti coating with a thickness of 0.2 mm, a Ni50Ti coating with a thickness of 0.3 mm, a Ni80Ti coating with a thickness of 0.3 mm, and a Ni22AA coating with a thickness of 0.4 mm from the titanium alloy blade to the Co-based alloy coating, the thickness of the Co-based alloy coating is 0.4 mm, and the thickness of the Co-based ceramic composite wear-resistant coating is 0.8 mm;

[0031] The raw material for preparing the Ni20Ti coating is Ni20Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 2:8; the raw material for preparing the Ni50Ti coating is Ni50Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 5:5; the raw material for preparing the Ni80Ti coating is Ni80Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 8:2; the raw material for preparing the Ni-based alloy coating is Ni22AA powder with a particle size of 45μm to 106μm and a hardness lower than 250HV.

[0032] The raw material for preparing the Co-based alloy coating is Stellite 6 powder with a particle size of 45 μm to 150 μm;

[0033] The raw materials for preparing the Co-based ceramic composite wear-resistant coating include Co-based alloy powder and ceramic powder, wherein the Co-based alloy powder is Stellite 6 powder with a particle size of 45μm to 150μm, the ceramic powder is TiN, and the ceramic powder particle size is 15μm to 45μm, and the ceramic phase mass accounts for 20% in the Co-based ceramic composite wear-resistant coating.

[0034] The preparation method of the composite high-temperature wear-resistant gradient coating for titanium alloy blades in this embodiment comprises the following steps:

[0035] Step 1: grinding the titanium alloy blade, and then using anhydrous ethanol for ultrasonic cleaning to remove surface impurities and oxides and increase the roughness to obtain a treated titanium alloy blade;

[0036] Step 2: ball-milling Stellite 6 powder and TiN powder under Ar atmosphere to obtain Co-based ceramic composite wear-resistant coating powder; the grinding balls used in the ball-milling are stainless steel grinding balls, and the ball-to-material ratio is 1:5, the ball-milling time is 2 hours, and the ball-milling speed is 200 r / min;

[0037] Step 3, putting the Co-based ceramic composite wear-resistant coating powder obtained in step 2 and the Ni20Ti powder, Ni50Ti powder, Ni80Ti powder, Ni22AA powder, and Stellite6 powder into a vacuum dryer for drying and dehumidification to obtain dried powders; the drying and dehumidification temperature is 100° C. and the time is 2 hours;

[0038] Step 4: In an argon atmosphere with an oxygen content of less than 100 ppm, using the dried powders obtained in step 3 as raw materials, laser cladding of a Ni-Ti transition coating, a Co-based alloy coating, and a Co-based ceramic composite wear-resistant coating is performed on the treated titanium alloy blade obtained in step 1 in sequence to form a composite high-temperature wear-resistant gradient coating;

[0039] The laser cladding process parameters of the Ni-Ti transition coating are: laser power 0.8 kW, scanning speed 12 mm / s, overlap rate 60%, powder carrier gas flow rate 6 L / min, powder feeding speed 7 g / min, spot diameter 2 mm;

[0040] The laser cladding process parameters of the Co-based alloy coating and the Co-based ceramic composite wear-resistant coating are: laser power 1.2 kW, scanning speed 12 mm / s, overlap rate 50%, powder-carrying gas flow argon gas flow 6 L / min, powder feeding speed 7 g / min, and spot diameter 2 mm.

[0041] After testing, the thickness of the composite high-temperature wear-resistant gradient coating specially prepared for the titanium alloy blade in this embodiment is 2.4 mm. After being used 300 times under high-temperature conditions, no falling off or cracking was observed, showing good high-temperature resistance. The coating hardness is 720 HV, and the coating loss is 13.3 mg / h under the friction condition of 200 N. Compared with the titanium alloy blade substrate, the wear resistance is improved by more than 20 times.

[0042] Example 2

[0043] like Figure 1As shown, the composite high-temperature wear-resistant gradient coating dedicated to the titanium alloy blade in this embodiment includes a Ni-Ti transition coating, a Co-based alloy coating, and a Co-based ceramic composite wear-resistant coating that are sequentially laser-clad on the surface of the titanium alloy blade; the composition of the Ni-Ti transition coating is a Ni20Ti coating with a thickness of 0.4 mm, a Ni50Ti coating with a thickness of 0.4 mm, a Ni80Ti coating with a thickness of 0.4 mm, and a Ni22AA coating with a thickness of 0.6 mm from the titanium alloy blade to the Co-based alloy coating, the thickness of the Co-based alloy coating is 0.7 mm, and the thickness of the Co-based ceramic composite wear-resistant coating is 1.2 mm;

[0044] The raw material for preparing the Ni20Ti coating is Ni20Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 2:8; the raw material for preparing the Ni50Ti coating is Ni50Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 5:5; the raw material for preparing the Ni80Ti coating is Ni80Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 8:2; the raw material for preparing the Ni-based alloy coating is Ni22AA powder with a particle size of 45μm to 106μm and a hardness lower than 250HV.

[0045] The raw material for preparing the Co-based alloy coating is Stellite 12 powder with a particle size of 45 μm to 150 μm;

[0046] The raw materials for preparing the Co-based ceramic composite wear-resistant coating include Co-based alloy powder and ceramic powder, wherein the Co-based alloy powder is Stellite 12 powder with a particle size of 45μm to 150μm, the ceramic powder is TiC, and the ceramic powder particle size is 15μm to 45μm, and the ceramic phase mass accounts for 40% in the Co-based ceramic composite wear-resistant coating.

[0047] The preparation method of the composite high-temperature wear-resistant gradient coating for titanium alloy blades in this embodiment comprises the following steps:

[0048] Step 1: grinding the titanium alloy blade, and then using anhydrous ethanol for ultrasonic cleaning to remove surface impurities and oxides and increase the roughness to obtain a treated titanium alloy blade;

[0049] Step 2: ball-milling the Stellite 12 powder and the TiC powder under an Ar atmosphere to obtain a Co-based ceramic composite wear-resistant coating powder; the grinding balls used in the ball-milling are stainless steel grinding balls, and the ball-to-material ratio is 1:5, the ball-milling time is 3 hours, and the ball-milling speed is 250 r / min;

[0050] Step 3, the Co-based ceramic composite wear-resistant coating powder obtained in step 2, as well as Ni20Ti powder, Ni50Ti powder, Ni80Ti powder, Ni22AA powder, and Stellite 12 powder are placed in a vacuum dryer for drying and dehumidification to obtain dried powders; the drying and dehumidification temperature is 100° C. and the time is 2 hours;

[0051] Step 4: In an argon atmosphere with an oxygen content of less than 100 ppm, using the dried powders obtained in step 3 as raw materials, laser cladding of a Ni-Ti transition coating, a Co-based alloy coating, and a Co-based ceramic composite wear-resistant coating is performed on the treated titanium alloy blade obtained in step 1 in sequence to form a composite high-temperature wear-resistant gradient coating;

[0052] The laser cladding process parameters of the Ni-Ti transition coating are: laser power 1.0 kW, scanning speed 14 mm / s, overlap rate 60%, powder carrier gas flow rate 8 L / min, powder feeding speed 8 g / min, spot diameter 2 mm;

[0053] The laser cladding process parameters of the Co-based alloy coating and the Co-based ceramic composite wear-resistant coating are: laser power 1.4 kW, scanning speed 16 mm / s, overlap rate 50%, powder-carrying gas flow argon gas flow 8 L / min, powder feeding speed 8 g / min, and spot diameter 2 mm.

[0054] After testing, the thickness of the composite high-temperature wear-resistant gradient coating specially prepared for the titanium alloy blade in this embodiment is 3.7 mm. After being used 300 times under high-temperature conditions, no falling off or cracking was observed, showing good high-temperature resistance. The coating hardness is 700 HV, and the coating loss is 15.6 mg / h under the friction condition of 200 N. Compared with the titanium alloy blade substrate, the wear resistance is improved by more than 18 times.

[0055] Example 3

[0056] like Figure 1 As shown, the composite high-temperature wear-resistant gradient coating dedicated to the titanium alloy blade in this embodiment includes a Ni-Ti transition coating, a Co-based alloy coating, and a Co-based ceramic composite wear-resistant coating that are sequentially laser-clad on the surface of the titanium alloy blade; the composition of the Ni-Ti transition coating is a Ni20Ti coating with a thickness of 0.3 mm, a Ni50Ti coating with a thickness of 0.35 mm, a Ni80Ti coating with a thickness of 0.35 mm, and a Ni22AA coating with a thickness of 0.5 mm from the titanium alloy blade to the Co-based alloy coating, the thickness of the Co-based alloy coating is 0.6 mm, and the thickness of the Co-based ceramic composite wear-resistant coating is 1.0 mm;

[0057] The raw material for preparing the Ni20Ti coating is Ni20Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 2:8; the raw material for preparing the Ni50Ti coating is Ni50Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 5:5; the raw material for preparing the Ni80Ti coating is Ni80Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 8:2; the raw material for preparing the Ni-based alloy coating is Ni22AA powder with a particle size of 45μm to 106μm and a hardness lower than 250HV.

[0058] The raw material for preparing the Co-based alloy coating is Stellite 12 powder with a particle size of 45 μm to 150 μm;

[0059] The raw materials for preparing the Co-based ceramic composite wear-resistant coating include Co-based alloy powder and ceramic powder, wherein the Co-based alloy powder is Stellite 12 powder with a particle size of 45μm to 150μm, the ceramic powder is TiB2, and the ceramic powder particle size is 15μm to 45μm, and the ceramic phase mass accounts for 30% in the Co-based ceramic composite wear-resistant coating.

[0060] The preparation method of the composite high-temperature wear-resistant gradient coating for titanium alloy blades in this embodiment comprises the following steps:

[0061] Step 1: grinding the titanium alloy blade, and then using anhydrous ethanol for ultrasonic cleaning to remove surface impurities and oxides and increase the roughness to obtain a treated titanium alloy blade;

[0062] Step 2: ball-milling the Stellite 12 powder and the TiB2 powder under an Ar atmosphere to obtain a Co-based ceramic composite wear-resistant coating powder; the grinding balls used in the ball-milling are stainless steel grinding balls, and the ball-to-material ratio is 2:5, the ball-milling time is 2.5 hours, and the ball-milling speed is 230 r / min;

[0063] Step 3, putting the Co-based ceramic composite wear-resistant coating powder obtained in step 2 and the Ni20Ti powder, Ni50Ti powder, Ni80Ti powder, Ni22AA powder, and Stellite6 powder into a vacuum dryer for drying and dehumidification to obtain dried powders; the drying and dehumidification temperature is 100° C. and the time is 2 hours;

[0064] Step 4: In an argon atmosphere with an oxygen content of less than 100 ppm, using the dried powders obtained in step 3 as raw materials, laser cladding of a Ni-Ti transition coating, a Co-based alloy coating, and a Co-based ceramic composite wear-resistant coating is performed on the treated titanium alloy blade obtained in step 1 in sequence to form a composite high-temperature wear-resistant gradient coating;

[0065] The laser cladding process parameters of the Ni-Ti transition coating are: laser power 0.9k, scanning speed 13mm / s, overlap rate 60%, powder carrier gas flow rate 7L / min, powder feeding speed 8g / min, spot diameter 2mm;

[0066] The laser cladding process parameters of the Co-based alloy coating and the Co-based ceramic composite wear-resistant coating are: laser power 1.3kW, scanning speed 15mm / s, overlap rate 50%, powder-carrying gas flow argon gas flow 7L / min, powder feeding speed 8g / min, and spot diameter 2mm.

[0067] After testing, the thickness of the composite high-temperature wear-resistant gradient coating specially prepared for the titanium alloy blade in this embodiment is 3.1 mm. After being used 300 times under high-temperature conditions, no falling off or cracking was observed, showing good high-temperature resistance. The coating hardness is 640 HV, and the coating loss is 18.7 mg / h under the friction condition of 200 N. Compared with the titanium alloy blade substrate, the wear resistance is improved by more than 17 times.

[0068] Example 4

[0069] The difference between this embodiment and embodiment 1 is that the raw material ceramic powder for preparing the Co-based ceramic composite wear-resistant coating is WC-xCo, where x is 10.

[0070] After testing, the special titanium alloy blade composite high-temperature wear-resistant gradient coating prepared in this embodiment has a thickness of 2.4 mm. After being used 300 times under high-temperature conditions, no falling off or cracking was observed, showing good high-temperature resistance. The coating hardness is 770 HV, and the coating loss is 11.3 mg / h under the friction condition of 200 N. Compared with the titanium alloy blade substrate, the wear resistance is improved by more than 22 times.

[0071] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A composite high-temperature wear-resistant gradient coating specially used for titanium alloy blades, characterized in that: It comprises a Ni-Ti transition coating, a Co-based alloy coating and a Co-based ceramic composite wear-resistant coating which are sequentially laser-clad on the surface of a titanium alloy blade. The composition of the Ni-Ti transition coating shows a trend of a gradual decrease in Ti element content and a gradual increase in Ni element content along the direction from the titanium alloy blade to the Co-based alloy coating.

2. The composite high-temperature wear-resistant gradient coating for titanium alloy blade according to claim 1, characterized in that: The compositions of the Ni-Ti transition coating are Ni20Ti coating, Ni50Ti coating, Ni80Ti coating and Ni-based alloy coating in the direction from the titanium alloy blade to the Co-based alloy coating.

3. The composite high-temperature wear-resistant gradient coating for titanium alloy blade according to claim 2, characterized in that: The raw material for preparing the Ni20Ti coating is Ni20Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 2:8; the raw material for preparing the Ni50Ti coating is Ni50Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 5:5; the raw material for preparing the Ni80Ti coating is Ni80Ti powder with a particle size of 53μm to 150μm and an atomic ratio of Ni to Ti of 8:2; the raw material for preparing the Ni-based alloy coating is Ni-based alloy powder with a particle size of 45μm to 106μm and a hardness lower than 250HV.

4. The composite high-temperature wear-resistant gradient coating for titanium alloy blade according to claim 1, characterized in that: The raw material for preparing the Co-based alloy coating is Stellite 6 or Stellite 12 Co-based alloy powder with a particle size of 45 μm to 150 μm.

5. The composite high-temperature wear-resistant gradient coating for titanium alloy blade according to claim 1, characterized in that: The raw materials for preparing the Co-based ceramic composite wear-resistant coating include Co-based alloy powder and ceramic powder, wherein the Co-based alloy powder is of the same type as the raw material for preparing the Co-based alloy coating, the ceramic powder is selected from nitride TiN, carbide TiC, WC-xCo or boride TiB2, and the particle size of the ceramic powder is 15μm to 45μm; the mass proportion of the ceramic phase in the Co-based ceramic composite wear-resistant coating is 20% to 40%.

6. The composite high-temperature wear-resistant gradient coating for titanium alloy blades according to claim 2, characterized in that: The thickness of the Ni20Ti coating is 0.2mm-0.4mm, the thickness of the Ni50Ti coating is 0.3mm-0.4mm, the thickness of the Ni80Ti coating is 0.3mm-0.4mm, the thickness of the Ni-based alloy coating is 0.4mm-0.6mm, the thickness of the Co-based alloy coating is 0.4mm-0.7mm, and the thickness of the Co-based ceramic composite wear-resistant coating is 0.8mm-1.2mm.

7. A method for preparing a composite high temperature wear-resistant gradient coating as claimed in any one of claims 1 to 6, characterized in that: The method comprises the following steps: Step 1: grinding the titanium alloy blade, and then using anhydrous ethanol for ultrasonic cleaning to remove surface impurities and oxides and increase the roughness to obtain a treated titanium alloy blade; Step 2: ball-milling the Co-based alloy powder and the ceramic powder in an Ar atmosphere to obtain a Co-based ceramic composite wear-resistant coating powder; Step 3, the Co-based ceramic composite wear-resistant coating powder obtained in step 2, as well as Ni20Ti powder, Ni50Ti powder, Ni80Ti powder, Ni-based alloy powder, and Co-based alloy powder are placed in a vacuum dryer for drying and dehumidification to obtain dried powders; the drying and dehumidification temperature is 100° C. and the time is 2 hours; Step 4: Under an argon atmosphere, using the dried powders obtained in step 3 as raw materials, laser cladding of Ni-Ti transition coating, Co-based alloy coating and Co-based ceramic composite wear-resistant coating is performed in sequence on the treated titanium alloy blade obtained in step 1 to form a composite high-temperature wear-resistant gradient coating.

8. The method according to claim 7, characterized in that The grinding balls used for ball milling and mixing in step 2 are stainless steel grinding balls, and the ball-to-material ratio is 1-2:5, the ball milling time is 2h-3h, and the ball milling speed is 200r / min-250r / min; the oxygen content in the argon atmosphere in step 4 is less than 100ppm.

9. The method according to claim 7, characterized in that: The laser cladding process parameters of the Ni-Ti transition coating are: laser power 0.8kW~1.0kW, scanning speed 12mm / s~14mm / s, overlap rate 60%, powder carrier gas flow argon gas flow 6L / min~8L / min, powder feeding speed 7g / min~8g / min, spot diameter 2mm.

10. The method according to claim 7, characterized in that The laser cladding process parameters of the Co-based alloy coating and the Co-based ceramic composite wear-resistant coating are: laser power 1.2kW~1.4kW, scanning speed 12mm / s~16mm / s, overlap rate 50%, powder carrier gas flow rate 6L / min~8L / min, powder feeding speed 7g / min~10g / min, and spot diameter 2mm.

Citation Information

Cited By

  • Acupuncture needle for treating drastic bag

    CN120267525A

  • Titanium alloy push broach and surface modification method of titanium alloy push broach

    CN122588524A